AMPLIFICATION BY ANONYMITY, AN UNASSUMING TOOL OF CYBERBULLYING - Ando, Andrei; Ozarchevici, Mihaela (International Journal of Legal and Social Order, 2024)
The paper explores the phenomenon of amplification through anonymity as a form of cyber-bullying in the Romanian media, highlighting how online anonymity influences user behavior, through what specialists call "the effect of online disinhibition." In the absence of personal responsibility and identification, users have the possibility of posting multiple comments under different pseudonyms, inducing the perception of a broad consensus around certain opinions. This phenomenon is known as the "False Consensus Effect" and is often used to create false impressions on public opinion, manipulating readers' perceptions and increasing psychological pressure on targets. Diaz and Nilsson (2023) have shown that internet manipulation often tends to alter individuals’ behavior. By accepting their comments, by generating a group of supporters, they feel entitled to expose a point of view, to support it beyond the limits of accepted social conventions. In the 2000s, the concept of "cognitive hacking" was launched and it is detailed in the research of Thompson, Trevisani and Sisti (2004). Cognitive hacking is actually a cyber attack against an individual, likely to change the perception and behavior of others towards him. At the same time, the paper highlights how some publications contribute to this manipulation through selective editorial filters and even by involving journalists in comment sections, using a subjective tone, contrary to the editorial objectivity they should respect. Also, the comment rating systems (through upvotes or ratings) are susceptible to manipulation, allowing users to self-amplify their opinion and create the illusion of collective support. Legally, these practices raise issues related to disinformation and manipulation of public opinion, but also to the responsibility of platforms and publications towards user-generated content. According to the legislation of online communication and protection against cyberbullying, there is a need for stricter regulation of anonymity and editorial control mechanisms. The European Union, for example, has adopted a series of legislative measures in this regard, through the Digital Services Act (DSA), which requires social media platforms to limit the abuse of anonymity and make users responsible for the content posted. Also in this context, a simple and effective mechanism for moral sanitation of the online press forum is at the disposal of editors: filtering comments, as well as displaying the IP address, are ways to highlight multiple comments posted by the same user under different nicknames. Starting from these ideas, the paper proposes an interdisciplinary analysis, examining from a journalistic, sociological and legal point of view the challenges brought by online anonymity and its role in amplifying cyber-bullying phenomena.